Measurement properties of the Star Excursion Balance Test in patients with ACL deficiency. (March 2019) - Dobija, Lech; Reynaud, Vivien; Pereira, Bruno; Van Hille, William; Descamps, Stephane; Bonnin, Armand; Coudeyre, Emmanuel
Abstract: Objectives: To assess intrarater reliability, agreement and construct validity of the Star Excursion Balance Test (SEBT) in individuals with anterior cruciate ligament (ACL) deficiency and the ability of the SEBT to distinguish between healthy and ACL-deficient individuals. Methods: Patients with ACL deficiency and healthy matched controls performed the SEBT and the One Leg Hop for Distance test (OLHD). Three consecutive trials were analyzed. Also evaluated were isokinetic thigh muscle strength and self-reported function. Results: We included 33 patients and 33 matched controls. Intrarater reliability of the SEBT was good to excellent (ICC: 0.88–0.96). Agreement was estimated by the minimal detectable change (5.93–8.36 cm). Posteromedial and posterolateral direction and composite score of the SEBT were correlated with OLHD performance ( r : 0.34–0.53, p  < 0.05) and thigh muscle strength ( r : 0.35–0.45, p  < 0.05). Posteromedial and posterolateral direction and composite scores of the SEBT were significantly lower bilaterally for patients with ACL deficiency than controls ( p  < 0.05). Conclusion: The SEBT can be used in patients with ACL deficiency with good to excellent intrarater reliability. Construct validity of the SEBT versus the OLHD test and isokinetic thigh muscle strength can be confirmed. Furthermore, posteromedial and posterolateral performance of the SEBT can detect bilateral neuromuscular control deficits. Highlights: The SEBT has good to excellent intrarater reliability in patients with ACL deficiency. Construct validity of the posteromedial and posterolateral SEBT versus OLHD test, versus muscle strength is confirmed. The posteromedial and posterolateral SEBT detect bilateral deficits in individuals with ACL deficiency.